2020
DOI: 10.1128/jvi.00029-20
|View full text |Cite
|
Sign up to set email alerts
|

BPIFB3 Regulates Endoplasmic Reticulum Morphology To Facilitate Flavivirus Replication

Abstract: Flaviviruses, including dengue virus (DENV) and Zika virus (ZIKV), rely heavily on the availability of endoplasmic reticulum (ER) membranes throughout their life cycle, and degradation of ER membranes restricts flavivirus replication. Accordingly, DENV and ZIKV restrict ER turnover by protease-mediated cleavage of reticulophagy regulator 1 (RETREG1), also known as FAM134B, an autophagy receptor responsible for targeted ER sheet degradation. Given that the induction of autophagy may play an important role in fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
40
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 47 publications
11
40
2
Order By: Relevance
“…Given that BPIFB3 regulates a non-canonical autophagy pathway, we sought to characterize which components of the autophagic initiation machinery were required for the induction of autophagy during BPIFB3 depletion. To do this, we used two distinct viruses, CVB and DENV, as read outs for the reversal of autophagy induction given that our previous studies showed that BPIFB3-induced autophagy increases the replication of CVB, while it restricts DENV infection (Delorme-Axford et al, 2014;Evans et al, 2020). We tested components associated with three key phases of autophagy induction-autophagosome nucleation (ULK1), isolation membrane formation (the catalytic component of PI3K (PI3KC3), UVRAG1, and BECN1), and processing of LC3 (ATG7).…”
Section: Bpifb3 Depletion-induced Autophagy Does Not Rely On Canonicamentioning
confidence: 99%
See 4 more Smart Citations
“…Given that BPIFB3 regulates a non-canonical autophagy pathway, we sought to characterize which components of the autophagic initiation machinery were required for the induction of autophagy during BPIFB3 depletion. To do this, we used two distinct viruses, CVB and DENV, as read outs for the reversal of autophagy induction given that our previous studies showed that BPIFB3-induced autophagy increases the replication of CVB, while it restricts DENV infection (Delorme-Axford et al, 2014;Evans et al, 2020). We tested components associated with three key phases of autophagy induction-autophagosome nucleation (ULK1), isolation membrane formation (the catalytic component of PI3K (PI3KC3), UVRAG1, and BECN1), and processing of LC3 (ATG7).…”
Section: Bpifb3 Depletion-induced Autophagy Does Not Rely On Canonicamentioning
confidence: 99%
“…This regulation of autophagy has been demonstrated to have important implications in regulating the infection of two distinct families of viruses, enteroviruses and flaviviruses. Depletion of BPIFB3 specifically enhances the replication capacity of the enterovirus CVB, while restricting the replication of the two flaviviruses DENV and ZIKV (Delorme-Axford et al, 2014;Evans et al, 2020). These disparate impacts on replication highlight key replication differences between the two families of viruses and their sensitivity to turnover by BPIFB3-regulated autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations